A learning curve in using orphan liver allografts for transplantation. Issue 4 (9th March 2020) - Rana, Abbas; Joshi, Manasi; Price, Matthew Brent; Ganni, Saif; Bakhtiyar, Syed S.; Vierling, John M.; Galvan, Nhu Thao; Cotton, Ronald T.; O'Mahony, Christine A.; Kanwal, Fasiha; Goss, John A.
Abstract: Given the critical shortage of donor livers, marginal liver allografts have potential to increase donor supply. We investigate trends and long‐term outcomes of liver transplant using national share allografts transplanted after rejection at the local and regional levels. We studied a cohort of 75 050 candidates listed in the Organ Procurement and Transplantation Network for liver transplantation between 2002 and 2016. We compared patients receiving national share and regional/local share allografts from 2002‐2006, 2007‐2011, and 2012‐2016, performing multivariate Cox regression for graft survival. Recipient and center‐level covariates that were not significant ( P  < .05) were removed. Graft survival of national share allografts improved over time. National share allografts had a 26% increased risk for graft failure in 2002‐2006 but no impact on graft survival in 2007‐2011 and 2012‐2016. The cold ischemia time (CIT) of national share allografts decreased from 10.4 to 8.0 hours. We demonstrate that CIT had significant impact on graft survival using national share allografts (CIT <6 hours: hazard ratio 0.75 and CIT >12 hours: hazard ratio 1.25). Despite a trend toward sicker recipients and poorer quality allografts, graft survival outcomes using national share allografts have improved to benchmark levels. Reduction in cold ischemia time is a possible explanation.